The role of support morphology on the performance of Cu/ZnO-catalyst for hydrogenation of CO 2 to methanol - Tasfy, S.F.H. (American Institute of Physics Inc., 2015)
The effects of SBA-15 support morphology on the activity of Cu/ZnO catalyst in the hydrogenation of CO 2 to methanol was investigated. In the hydrogenation of CO 2 to methanol at 210Â°C, 2.25 MPa, H 2 /CO 2 ratio of three remarkable difference was obtained using Cu/ZnO catalyst supported on SBA-15 with different morphology. The catalysts were characterized using N 2 -adsorption, field emission scanning microscopy (FESEM/EDX), transmission electron microscopy (HRTEM), and temperature-programmed reduction (TPR). Characterization of the catalyst showed that support morphology, surface area, metals dispersion, and reducibility influenced the catalytic performance. On the fiber-shaped SBA-15, copper dispersion was 29 whereas on the spherical-shaped SBA-15, the dispersion was 20 . The experimental results showed that the catalyst supported over fiber-shaped SBA-15 exhibit higher CO 2 conversion (13.96 ) and methanol selectivity (91.32 ) compare to catalyst supported over spherical-shaped SBA-15. Â© 2015 AIP Publishing LLC.